1974
DOI: 10.1128/jvi.13.1.73-80.1974
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Membrane Protein Synthesized After Infection with Bacteriophage T4

Abstract: The synthesis of membrane protein after infection with bacteriophage T4 was examined. Protein constituents of both the cytoplasmic and outer membrane are made during the infective cycle. In addition, newly synthesized membrane protein is found in material which has a buoyant density greater than that of either of the two host membrane fractions. Polyacrylamide gel analyses and solubilization studies using the detergent Sarkosyl indicate that synthesis of most of the membrane proteins made during the first 5 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Extraction of membranes with Sarkosyl selectively extracts membrane proteins without affecting those of the cell wall (1,12,13). Conse-quently, this agent can be used to discriminate between cytoplasmic membrane (Sarkosyl-soluble) and cell wall (Sarkosyl-insoluble) proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extraction of membranes with Sarkosyl selectively extracts membrane proteins without affecting those of the cell wall (1,12,13). Conse-quently, this agent can be used to discriminate between cytoplasmic membrane (Sarkosyl-soluble) and cell wall (Sarkosyl-insoluble) proteins.…”
Section: Resultsmentioning
confidence: 99%
“…For example, 1-lactate dehydrogenase is solubilized by chaotropic agents (20). Subsequent extraction of guanidinetreated membranes with the detergent Sarkosyl selectively extracts the cytoplasmic membrane proteins without affecting those of the cell wall (1,12,13).…”
Section: Am__~~~a Lmentioning
confidence: 99%
See 1 more Smart Citation
“…LITERATURE CITED 1. Beckey, A. D., J. L. Wulff, and C. F. Earhart. 1974. Early synthesis of membrane protein after bacteriophage T4 infection.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…However, until recently little had been done to establish the cellular location of these proteins. Recent work on T4 and, to a lesser extent, on T5 has shown that many phage-induced proteins are associated with the host envelope (1, 4,6,9,10,14,15,18,20).…”
mentioning
confidence: 99%